Rozpowszechnienie wybranych czynników ryzyka raka piersi wśród pacjentek - Bojakowska, Urszula Jolanta; Kalinowski, Paweł; Kowalska, Marta Estera (Journal of Education, Health and Sport, 2017)
Introduction The development of breast cancer is related to the influence of various risk factors. Aim The aim of the study was to analyze the prevalence of selected breast cancer risk factors in patients with breast cancer. Material and method The study was conducted in the period from September 2015 until April 2016. The method of diagnostic survey. The research tool was the original questionnaire. In total, data were collected from 200 patients with breast cancer. Data were analyzed using descriptive statistics methods. Results More than 20% of women declared breast cancer in the family. 28.5% in the past suffered from other forms of cancer such as thyroid cancer, adrenal, skin. Most patients did not provide information on other breast diseases in the past. A slightly higher percentage of the examined women (32.5%) declared that before the diagnosis of breast cancer, mammography had ever seenchanges with an increased density of the glandular breast tissue. Conclusions 1. Among the risk factors that have been observed in the analyzed group are the familial burden of breast cancer and other cancers, as well as the incidence of other cancers in the past. 2. The analysis showed that in the group of examined women there was a problem of increased density of breast tissue. 3. Most of the respondents negate occurence of other breast diseases in the past.